The Role of Stakeholders in Managing Social Forestry Business Development in FMU South Bandung, Indonesia - Hidayat, Fakhri Rhamadian; Bahruni; Trison, Soni (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Social forestry symbolizes a sustainable forest management strategy, where local communities are important in strengthening socio-economic aspects, namely welfare and environmental sustainability. Increasing community welfare depends on collective efforts of social forestry, regional regulations, institutional structures, and cooperative with various stakeholders. Subsequent analysis employed the stakeholder analysis model, which scrutinizes stakeholders' roles in natural resource management. The examination compares roles outlined in policy with stakeholders' actual engagement. Consequently, the research provides insights into how stakeholders contribute to social forestry business development based on two critical factors: interest and influence. Results indicate that stakeholders' roles and contributions are substantially influenced by policy, especially concerning their interests and impact on community business ventures in social forestry. Stakeholder analysis reveals that governmental bodies, as mandated by policy, predominantly occupy quadrant II, tasked with aiding community groups in advancing social forestry businesses. However, quadrant I also encompasses governmental entities, albeit with limited involvement in community group activities. QuadrantsIII and IV underscore the diverse roles stakeholders assume within their respective domains, reflecting their interests and influence on business development initiatives to empower the community and improve the livelihood. This research aims to formulate tactics to enhance stakeholder involvement in implementing nation policies for fostering social forestry enterprises within the FMU South Bandung. The tactics need support of each party, especially the social forestry regulation in developing the business and capacity agency in measurement of accessible market, business plan, valuable product and good forest institutions.